THE IMPACTS OF THE BEAUTY MYTH ON THE EXISTENTIAL FREEDOM OF PECOLA IN TONI MORRISONâS THE BLUEST EYE - Asmarani, Ratna (Language Circle: Journal of Language and Literature, 2016)
The purpose of this paper is to analyse the destructive impacts of the beauty myth on the existential freedom of Pecola, the young, poor, black female character, in Toni Morrisonâs âThe Bluest Eye.â The analysis is done through feminist criticism supported by the concept of the beauty myth and beauty as well as Sartrean concept of existentialism. The result shows that the widely spread beauty myth blocks Pecolaâs existential freedom on the physical, consciousness, or social life level. All these lead to young Pecolaâs ruined existence.